Right and Wrong: Assessing Scalar Consequentialism - McElwee, Brian (Ethical theory and moral practice, 2024)
Demoralising ethical theory involves eschewing the deontic categories of moral obligation, moral permissibility, and moral impermissibility from our ethical thought. In this paper, I evaluate the case made in Alastair Norcross’s recent book, Morality By Degrees (2020), for a consequentialist version of such demoralisation. Norcross defends scalar consequentialism, a radical variant of consequentialism which restricts fundamental normative verdicts to a scalar ranking of available actions, ordered according to the goodness of the consequences they produce. Following an introductory Sect. 1, I assess the positive case for scalar consequentialism in Sect. 2, concluding that no strong case has been made for the view. In Sect. 3, I assess the case against the view, concluding that while scalar consequentialism may be able to avoid the action-guidingness objection, it falls foul of the force objection. In Sect. 4, I expand on this critique, showing that Norcross gives an unstable account of how to assess attitudes, such as desires, beliefs and emotions. In Sect. 5, I argue that appeal to a contextualist reductionism does little to make the scalar view appealing.